Do Conceptual Innovations Facilitate Transformative Change? The Case of Biodiversity Governance - Hysing, Erik; Lidskog, Rolf (Frontiers in Ecology and Evolution, 2021)
This paper explores to what extent and in what ways conceptual innovations matter for biodiversity policy and implementation. The background is the continued loss of biodiversity and ecosystem degradation which have dramatically increased the need for transformative change. Conceptual innovations are a central means to engage and convince politicians, corporations, and citizens on the values nature, and to foster transformative changes. However, because of lack of substantial progress, questions have been raised on what is needed for new conceptualizations to have substantial impact on biodiversity politics and practices. This study is explorative, investigating how scientific concepts are discussed in research and in practice, using the concept of Ecosystem Service to investigate how concepts matter for policy development and transformative change in biodiversity governance. This is done in three steps: As a first step, it describes how concepts matter for policy development and transformative change. Thereafter it explores the academic debate on the transformative power of the concept ecosystem services. As a third step, it makes an in-depth study of how policy actors in Sweden use and value ecosystem services. Based on this investigation, the paper returns to the general questions on how conceptual innovations can generate transformative changes, and what is important to consider when developing concepts – such as Nature’s Contribution to People – with the aim to better facilitate transformative change.